Measuring the Poisson’s Ratio of Fibronectin Using Engineered Nanofibers - Szymanski, John M. (Sci Rep, 2017)
The extracellular matrix (ECM) is a fibrillar protein-based network, the physical and chemical properties of which can influence a multitude of cellular processes. Despite having an important role in cell and tissue signaling, a complete chemo-mechanical characterization of ECM proteins such as fibronectin (FN) is lacking. In this study, we engineered monodisperse FN nanofibers using a surface-initiated assembly technique in order to provide new insight into the elastic behavior of this material over large deformations. FN nanofibers were patterned on surfaces in a pre-stressed state and when released from the surface underwent rapid contraction. We found that the FN nanofibers underwent 3.3-fold and 9-fold changes in length and width, respectively, and that the nanofiber volume was conserved. Volume was also conserved following uniaxial extension of the FN nanofibers of ~2-fold relative to the patterned state. This data suggests that the FN networks we engineered formed an incompressible material with a Poisson’s ratio of ~0.5. While the Poisson’s ratio of cells and other biological materials are widely estimated as 0.5, our experimental results demonstrate that for FN networks this is a reasonable approximation.